Removal and recovery of chromium and chromium speciation with MINTEQA2 - Kocaoba, S; Akcin, G (ELSEVIER SCIENCE BV, 2002)
Chromium(M) is commonly found in large quantities in tannery wastewaters. For this reason, the recovery of the chromium content of these wastewaters is necessary for environmental protection and economic reasons. Removal and recovery of chromium were carried out by using ion exchange resins. To this purpose, two weakly acidic exchange resins Amberlite IRC 76 and Amberlite IRC 718 and a strongly acidic exchange resin Amberlite IR 120 were used. Basic chromium sulphate [Cr-4(SO4)(5)(OH)(2)] solutions in different concentrations and pH were used in all experiments as tanning baths. The resins were prepared in two different ionic forms as Na+ and H+. The effects of concentration, pH, stirring time and resin amount were investigated. The concentration range varied between 5 and 100 mg l(-1), pH range was between I and 8, stirring time between 5 and 60, and resin amount was between 50 and 1000 mg. Stirring speed was 2000 rpm during all these experiments. Exchange capacities, moisture contents and optimum conditions of these resins were determined in batch system. The results obtained showed that Amberlite IRC 76 and 718 weakly acidic resins had shown better performance than Amberlite IR 120 strongly acidic resin for removal and recovery of chromium(M) in Na+ form. Optimum conditions were found as concentration 10 mg l(-1), pH 5, stirring time 20 min, and resin amount 250 mg. Furthermore, chromium(III) speciation was investigated for optimum concentration and pH with MINTEQA2 computer programme. The studied pH range was between 1 and 8 and concentration range was between 5 and 100 mg l(-1). Cr(OH)(2+) species were found to be dominant at pH 5 and 10 mg l(-1) concentration in batch studies. There was a correlation between experimental and computerised results. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: chromium; ion exchange resins; optimum conditions; speciation; TANNERY; Chemistry